Factory and workshop legislation and convent laundries, 1895–1907: campaigning for a Catholic exception. Issue 168 (November 2021) - Harrison, Bridget
Abstract: Convents and convent-run institutions occupied an undefined legal space during the late nineteenth century. As homes for unmarried women, they combined religious ideas of holy seclusion with contemporary ideas of the feminine private sphere. However, women religious were also major providers of charity and welfare in Britain and Ireland, with many running charitable institutions. This brought them in closer contact with the state. As factory and workshop legislation towards the end of the nineteenth century expanded to include laundries, Catholic politicians used this ambiguous societal role to argue that Magdalene asylums deserved less inspection than for-profit laundries. In so doing, they both re-enforced nuns' right to domestic privacy and promoted their operations as a social good. This created a legal exemption for convent-run laundries, which allowed them to operate with limited scrutiny or interference. An examination of the debates surrounding factory and workshop legislation from 1895 to 1907 exposes a precedent which continued well into the twentieth century.